Influence of the melt composition on the cathode current density in electrode reactions - Solіanyk, L.О. (Physics and Chemistry of Solid State, 2022)
Within the framework of the Dogonadze-Kuznetsov-Levich theory, using the model of isotropic spherically symmetric bands with a root dependence on the energy of density of states, an expression for discharge currents at the dielectric/electrolyte interfacial boundary was obtained. An approach to estimate average density of electronic levels from which heterogeneous charge transfer takes place is proposed. An expression for obtaining a numerical value of cathode current density was established. Conditions of surface conductivity occurrence of a dielectric in a saline melt without its prior metallization are formulated. It is substantiated that the type of surface conductivity depends on reorganization energy, energy of reactants and reaction products in electrode field, transmission coefficient and other values which are determined by chemical composition of electrolyte, and can be calculated by analytical or quantum chemical methods. It was established that the adsorption of carbon dioxide on the surface of dielectric leads to a significant polarization of surface towards conduction band. The width of the band gap decreases, but the dielectric character of the cluster does not change, there is no band overlapping, i.e. an electrode does not acquire semiconducting and semimetallic character of conductivity. At the same time, adsorption of ВO2– on electrode surface leads to a strong polarization of the surface cluster towards the valence band, whlist a the band gap width decreases slightly, less than in the case of carbon dioxide.